Evaluation of right ventricular function in fetuses with hypoplastic left heart syndrome using tissue Doppler techniques. (11th May 2015) - Axt‐Fliedner, R.; Graupner, O.; Kawecki, A.; Degenhardt, J.; Herrmann, J.; Tenzer, A.; Doelle, A.; Willruth, A.; Steinhard, J.; Gembruch, U.; Bahlmann, F.; Enzensberger, C.; et al.
ABSTRACT Objective The outcome of patients with hypoplastic left heart syndrome (HLHS) is influenced by right ventricular function. This study aimed to investigate whether differences in right ventricular function of fetuses with HLHS are present during gestation. Methods This was a prospective study comprising 14 fetuses with HLHS (28 measurements obtained in total) and 28 normal control fetuses (31 measurements obtained in total). The two groups were matched for gestational age. Ultrasound M‐mode was used to assess displacement of the tricuspid annulus. Spectral Doppler and myocardial tissue Doppler‐derived inflow and outflow velocities were assessed. Tricuspid valve peak early wave to peak active wave (E/A) ratio, the early wave to early diastolic annular relaxation velocity (E/E′) ratio and the tissue Doppler‐derived myocardial performance index (MPI′) were calculated. Results E‐wave velocity was significantly higher in fetuses with HLHS than in control fetuses (mean, 40.14 cm/s vs 35.47 cm/s; P < 0.05, respectively), and A‐wave velocity in fetuses with HLHS showed a tendency for higher values in the right ventricle compared with normal control fetuses, but this did not reach statistical significance (61.16 cm/s vs 54.64 cm/s; P = 0.08). The E/A ratio increased during gestation in controls, but this increase was not seen in HLHS fetuses. Peak annular velocity during atrial contraction (A′) and the E/E′ ratio were significantly lower in controls than in HLHS fetuses: 9.50 cm/s vs 10.39 cm/s (P < 0.05) and 5.77 vs 7.37 (P < 0.05), respectively. There were no differences for right‐ventricular MPI′ or tricuspid annular plane systolic excursion between HLHS fetuses and controls. Conclusion The results of this study show that altered right ventricular function in HLHS infants may develop antenatally. It is hoped that confirmation of these findings using Doppler‐independent techniques will lead to further exploration of ventricular function in HLHS fetuses. Consequently, parental counseling and postnatal management strategies could be influenced. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.